Kelingan Adminduk Program: Services are Getting Closer to the Community - Sastri, Adinda; Chairunisa, Mina; Wulandari, Sri (Indonesian Journal of Advanced Research, 2025)
This research discusses the Kelingan Adminduk Program Service Getting Closer to the Community. The main focus of this research is to understand and examine the Kelingan Adminduk program service so that it can be closer to the community. In this research, qualitative methods were applied through a series of data collection activities, namely through in-depth interviews, participant observation, and documentation. The theory used in this research is the public service theory according to Lijan Poltak Sinambela. Based on the findings of the field research, the Kelingan Adminduk program has been implemented well, but the transparency indicator is still constrained by a lack of human resources and limited enrollment tools. Unstable internet connections and SIAK application disruptions are also obstacles faced by officers. To address these challenges, the Cirebon District Population and Civil Registration Office has taken measures such as improving service quality, maintaining and developing infrastructure, conducting routine evaluations, and establishing an open discussion forum for the community.